The Audience of Radio and Television - Yahia, Taqiyeddine (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2024)
In conclusion, this pedagogical lecture series has navigated through the intricate realm of media audiences, aiming to providePedagogical Publication -The Audience of Radio and TelevisionPrepared by: Dr. Yahia Taqiyeddine 98 a comprehensive understanding of their definition, characteristics, evolution, and the factors that have influenced the study of audiences over time. We have explored the hidden motivations that drive audience studies and the evolving theoretical approaches that have shaped our understanding of how audiences interact with various media forms. From defining the term "audience" to unraveling the stages of audience evolution and examining the impact of satellite channels on audience patterns and dominant values, this series has sought to shed light on the dynamic relationship between audiences and media in a rapidly evolving digital landscape. Understanding the features of the media audience, their symbolic and socio-political dimensions, and the postmodern audience is essential in comprehending the evolving nature of media engagement. The emergence of the digital audience in the electronic space has brought forth new challenges and opportunities, necessitating an exploration of novel research methods to capture and analyze audience behavior effectively. As we reflect on the concepts of postmodernity and the postmodern audience, we recognize that the contemporary media landscape is characterized by complexity, diversity, and constant